KARAKTERISTIK DAN MANAJEMEN KONJUNGTIVITIS PASIEN RAWAT JALAN DI RUMAH SAKIT INDERA DENPASAR PERIODE JANUARI-APRIL 2014 - Insani, Maulidia Laela; Adioka, I Gede Made; Artini, IGA; Nova, Agung (E-Jurnal Medika Udayana; Vol 6 No 7 (2017): E-Jurnal Medika Udayana, 2017)
Conjunctivitis is a common disease in the community. Until now there has been no study to find out the characteristics and management of conjunctivitis in Denpasar. This study was conducted to find out the characteristics and management of out-patient with conjunctivitis in Indera Hospital Denpasar period January to April 2014. This study was descriptive, in which the data were retrospective and taken cross-sectionally on Juny 2014. From 160 cases found in Indera Hospital Denpasar during the period of January to April 2014, it was known that most cases were male (53.125%), age group 31 to 40 years old (18.75%), predilecting location in both eyes (59.375%) with clinical sign of red eye (100%). Mostly prescribed therapeutic agents for conjunctivitis are eye drop preparations with antibiotic and lubricant. Keywords: Conjunctivitis, Characteristics, Management